Estado, administración y políticas públicas en América Latina: un esbozo sobre su desarrollo. (2020)
This paper studied the development of the field of State, administration, and public policy in Latin America from the processes of autonomization, institutionalization, professionalization and disciplinary specialization. The actors (individuals), institutions (teaching and research centers), the production of the area, and the constitution of thematic academic networks were analyzed. To do this we conducted interviews and collected data from journals, undergraduate and graduate courses in official databases, and pages of professional associations. We built a general panorama of this process in the region, and then pointed out the progress in Argentina, Brazil and Mexico based on these dimensions. Finally we made a general balance of the sub-area in Latin America, discussing the notion rooted in the literature on the relative backwardness of the field.